A comparison of the original and simplified Pulmonary Embolism Severity Index - Venetz, Carmen; Jiménez, David; Méan, Marie; Aujesky, Drahomir (Thrombosis and Haemostasis, 2011)
The Pulmonary Embolism Severity Index (PESI) is a validated clinical prognostic model for patients with pulmonary embolism (PE). Recently, a simplified version of the PESI was developed. We sought to compare the prognostic performance of the original and simplified PESI. Using data from 15,531 patients with PE, we compared the proportions of patients classified as low versus higher risk between the original and simplified PESI and estimated 30-day mortality within each risk group. To assess the models’ accuracy to predict mortality, we calculated sensitivity, specificity, and predictive values and likelihood ratios for low-versus higher-risk patients. We also compared the models’ discriminative power by calculating the area under the receiver-operating characteristic curve. The overall 30-day mortality was 9.3%. The original PESI classified a significantly greater proportion of patients as low-risk than the simplified PESI (40.9% vs. 36.8%; p<0.001). Low-risk patients based on the original and simplified PESI had a mortality of 2.3% and 2.7%, respectively. The original and simplified PESI had similar sensitivities (90% vs. 89%), negative predictive values (98% vs. 97%), and negative likelihood ratios (0.23 vs. 0.28) for predicting mortality. The original PESI had a significantly greater discriminatory power than the simplified PESI (area under the ROC curve 0.78 [95% CI: 0.77–0.79] vs. 0.72 [95% CI: 0.71–0.74]; p<0.001). In conclusion, even though the simplified PESI accurately identified patients at low-risk of adverse outcomes, the original PESI classified a higher proportion of patients as low-risk and had a greater discriminatory power than the simplified PESI.Institution where the work was carried out: Division of General Internal Medicine, Bern University Hospital, Bern, Switzerland.
Keywords: Pulmonary Embolism Severity Index; prognosis